Clinical outcomes of bizygomatic with anterior implants for restoring atrophic maxilla and all-on-four implants for restoring mandible: A case report (Indian Journal of Case Reports, 2025)
Atrophic jaws present significant challenges for rehabilitation due to limited bone availability, which complicates traditional implant placement. This case report presents the clinical outcomes of using zygomatic implants for the maxilla and the All-on-Four concept for the mandible in a 57-year-old male with severe atrophy of maxillary and mandibular ridges. Two zygomatic implants were placed in the maxilla, along with four anterior conventional implants, while the All-on-Four technique was utilized in the mandible. The surgical procedure and prosthetic rehabilitation are described. Follow-up at one year showed excellent prosthetic stability, rapid osseointegration, and improved quality of life. This combined approach demonstrated successful rehabilitation without extensive bone grafting, offering immediate functionality and aesthetic improvement. This case highlights the efficacy of zygomatic implants and the All-on-Four concept in managing atrophic jaws, providing an alternative to traditional bone augmentation procedures. However, long-term studies are needed to establish these techniques as standard treatment protocols.